RECORD OF PACIFIC PARROT FISH YPSISCARUS OEDEMA (SNYDER) FROM GULF OF MANNAR - Lalmohan, R S; Gandhi, V (Indian Journal of Fisheries, 2011)
While studying the coral fishes of Gulf of Mannar an interesting parrot fish Ypsiscarus oedema of the Family Scaridae was collected on 14-5-1974 from the gill net at Vedalai (Gulf of Mannar). A review of the literature shows that our understanding of the parrot fishes of India is far from complete. Day (1889) recorded 10 species of Psuedoscarus from India while 15 species of Callyodon were reported by Munro (1955) from India and Ceylon and 8 species from Laccadives hy Jones and Kumaran (1965).